2020
DOI: 10.4103/jfmpc.jfmpc_1149_19
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of basal implants in compromised ridges

Abstract: Aim: The aim of the present study was to evaluate clinically, radiographically, and functionally the outcomes of immediately loaded basal implants when placed in patients with compromised bone/alveolar ridges. Materials and Methods: A total of 18 systemically healthy (9 male and 9 female) subjects with compromised bone with poor quantity or quality were included in the study. A total number of 57 implants was placed, out of which 26 implants were placed in maxilla and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 8 publications
0
0
0
Order By: Relevance
“…Basal implants and abutments are deemed to be biologically inert, with no adverse or unfavorable reaction with host tissues, due to which there is reduced gingival inflammation and hence a reduction in gingival index score [ 10 ]. Anuradha et al [ 11 ] found that the sulcular bleeding index value at baseline was 1.92 ±0.29, which decreased to 1.49 ±0.28 at one month and to 1.107 ±0.25 at the end of three months postoperatively. In our study, the average marginal bone loss was 1.480 ±38 mm, whereas the average crestal bone loss was 1.060 ±30 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Basal implants and abutments are deemed to be biologically inert, with no adverse or unfavorable reaction with host tissues, due to which there is reduced gingival inflammation and hence a reduction in gingival index score [ 10 ]. Anuradha et al [ 11 ] found that the sulcular bleeding index value at baseline was 1.92 ±0.29, which decreased to 1.49 ±0.28 at one month and to 1.107 ±0.25 at the end of three months postoperatively. In our study, the average marginal bone loss was 1.480 ±38 mm, whereas the average crestal bone loss was 1.060 ±30 mm.…”
Section: Discussionmentioning
confidence: 99%
“…The design of basal implants to achieve cortical bone anchorage indicates their use in challenging clinical scenarios, including rehabilitation of atrophic ridges. Basal implants can play a vital role in the rehabilitation of patients, where compromised quality and/or quantity of bones is present [ 9 ].…”
Section: Discussionmentioning
confidence: 99%